Ac-[K-Aib-C(3,9-Acm; 6,12-DFLC(Acm)KKESEK)]4-NH2 - Vasiliki Moulasioti; Evgenia Fotou; Vassilios Moussis; Vassilios Tsikaris (Molbank)
Chemoselective reactions have played a crucial role in the development of high-molecular-weight (>3000 Da) macromolecules with a branched architecture, particularly as peptides and epitope-based vaccines have emerged as promising tools for drug development. Based on this, in this study, we designed and synthesized the peptide macromolecule CH3CO-[K-Aib-C(3,9-CH2NHCOCH3; 6,12-DFLC(CH2NHCOCH3)KKESEK)]4-NH2 [Ac-K-Aib-C(3,9-Acm); 6,12-epitope)]4-NH2] using chemoselective thioether bond formation between the peptide carrier CPSOC (3,9 Acm) and the IAc-DFLC(Acm)KKESEK-NH2 peptide epitope. The conjugate was purified via RP-HPLC and characterized via HR-ESI-MS. The epitope D128FLCKKESEK137 derives from the lethal toxin, ammodytoxin A, from the V. ammodytes snake species, and it was synthesized using the SPPS Fmoc/tBu methodology and characterized via HR-ESI-MS and NMR techniques.